Campus Canopy, 1938-05-14 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1938)
Cabinet of Y; SGA Officers Hold Retreat -- Ruth Bryan Owen Rohde Will Lecture Here May 16 -- Students Hear Stanford On IRC Program -- Emory Team Conducts Vesper
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals